2011
DOI: 10.1080/1070289x.2011.656068
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Political Activism or Political Activism by Muslims? Secular and Religious Identities Amongst Muslim Arab Activists in the United States and United Kingdom

Abstract: Scholarship on Muslim political mobilisation in theWest has developed as an important counterpoint to public discourse, which has tended to cast Muslims as a threat to social cohesion, liberal democracy, and national security. But even as scholarly literature has shed light on civic participation among Muslims, it has sidelined the diversity of political identities and values that motivate them. Most, if not all, Muslims in the West find their identities politicised in some way, but the question of whether thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In our study, individuals were more likely to identify themselves as members of a movement defending the Palestinian cause, which indicated that their religious identity did not directly motivate their intention to engage in collective action. This finding seems to illustrate that religious identity is viewed as an aspect of an individual's personal life (see Nagel & Staeheli, 2011). Among Muslims in the West, Islam is perceived as a belief (faith) and personal identity, while political involvement typically occurs through a separate identity that is more secular (Nagel & Staeheli, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our study, individuals were more likely to identify themselves as members of a movement defending the Palestinian cause, which indicated that their religious identity did not directly motivate their intention to engage in collective action. This finding seems to illustrate that religious identity is viewed as an aspect of an individual's personal life (see Nagel & Staeheli, 2011). Among Muslims in the West, Islam is perceived as a belief (faith) and personal identity, while political involvement typically occurs through a separate identity that is more secular (Nagel & Staeheli, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…This finding seems to illustrate that religious identity is viewed as an aspect of an individual's personal life (see Nagel & Staeheli, 2011). Among Muslims in the West, Islam is perceived as a belief (faith) and personal identity, while political involvement typically occurs through a separate identity that is more secular (Nagel & Staeheli, 2011). Evidence for this argument comes from astudy by Klandermans (2014) on the role of dual identity in protest actions.…”
Section: Discussionmentioning
confidence: 95%
“…By limiting their analysis to Islamic religiosity, Nagel and Staeheli (2011) investigate the political values and secular attitudes of Muslim activists in the West. Their results point to a large variety of attitudes towards secular values.…”
Section: Contrasting Effects Of Religiosity and Religious Belonging Omentioning
confidence: 99%
“…The conceptual contributions of geographers regarding religion in the Middle East and diaspora settings are towards studies of religious pluralism (Gökariksel, 2009;Gökariksel & Secor, 2015)-how different beliefs (and nonbelief) coalesce, converse, and transform in progressively mobile and interconnected worlds and how belief is produced through social process. globally are housed in the Middle EastFor feminist scholars, exploring religious terrain means rereading faith and piety at the site of the body (Dwyer, 1999;Gökariksel, 2009;Gökariksel & Secor, 2012;Secor, 2002;McGinty, 2014), including the ordinary and sacred spaces and objects bodies inhabit and touch (Es, 2016, Evered & Evered, 2016, Gökariksel, 2012, Hammond, 2014, Mills, 2007, Rootham, 2015, Nagel & Staeheli, 2011. Threading through this work is a careful attention to place.…”
Section: Beliefmentioning
confidence: 99%